Education Policies and Taxation without Commitment - Sebastian Findeisen; Dominik Sachs (University of Mannheim, Department of Economics, 2014)
We study the implications of limited commitment on education and tax policies chosen by benevolent governments. Individual wages are determined by both innate abilities and education levels. Consistent with real world practices, the government can decide to subsidize different levels of education at different rates. Deviations from full commitment tend to make education policies more progressive, increasing the education subsidy for initially low skilled agents and decreasing it for initially high skilled agents. We provide suggestive cross-country correlations for this mechanism.
urn:nbn:de:bsz:180-madoc-366223
Keywords: H21; H23; I21; 330; Education Policies; Time-Inconsistency; Taxation; Inequality